Identification of a Novel Simian Immunodeficiency Virus-Infected African Green Monkey ( Chlorocebus tantalus ) Confirms that Tantalus Monkeys in Cameroon Are Infected with a Mosaic SIVagm Lineage - (:unkn) unknown (My University, 2020)
In this study we report on the identification of a simian immunodeficiency virus (SIV) infecting a Chlorocebus tantalus from Cameroon. The isolate, SIVagmTAN-CA1, was molecularly characterized by sequencing partial genome (∼4,000 bp) using the conventional Sanger method and the Oxford Nanopore Technology (ONT). In pol and gp41/nef SIVagmTAN-CA1 clusters with SIVagmSAB infecting Chlorocebus sabaeus from West Africa, whereas in env-gp120 it clusters with SIVagmTAN infecting C. tantalus from Central Africa. This mosaic structure is similar to that of a previously reported isolate infecting another tantalus monkey from Cameroon and confirms that the evolution of SIVagm is complex. Our data show that ONT sequencing gives results comparable with conventional Sanger sequencing on SIV and could help in distinguishing recombination and coinfection.
Keywords: African Research